2021
DOI: 10.20473/jovin.v2i2.30625
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Adolescent Post-Disaster Eruption of Mount Semeru: Literature Review

Abstract: Introduction:Indonesia sits on an active continental plate, surrounded by a series of very active volcanoes called the ring of fire. These conditions make Indonesia very vulnerable to disasters. Mount Semeru was observed to have experienced at least 57 eruptions or eruptions. The resilience possessed by adolescents can affect when the post-eruption disaster strikes.Methods:The strategy to determine the selection of studies that have been found, the author uses a protocol and evaluation uses the PRISMA Checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The cultural factors are faith, morals, an attitude of struggle and never giving up despite difficult circumstances, worship, community support, and religious communities. Furthermore, Rahmawati et al (2021), in their research on the resilience of adolescents who experienced the eruption of Mount Merapi, explained that resilience is significant for adolescents in disaster situations after mountain eruptions. Most adolescents in the region have moderate and high resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultural factors are faith, morals, an attitude of struggle and never giving up despite difficult circumstances, worship, community support, and religious communities. Furthermore, Rahmawati et al (2021), in their research on the resilience of adolescents who experienced the eruption of Mount Merapi, explained that resilience is significant for adolescents in disaster situations after mountain eruptions. Most adolescents in the region have moderate and high resilience.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can also be concluded that adolescent girls are not as resilient as adolescent boys. Supported by research by Lu et al (2020), Rahmawati et al (2021), and Stratta (Lu et al, 2013) found that women tend to be more sensitive and stressed when facing complex and stressful situations that can interfere with the resilience process. Therefore, seeing the phenomenon of the current escape tragedy that befell the Rohingya ethnic community, researchers are interested in researching resilience and resilient sources obtained from adolescent female Rohingya survivors stranded in Aceh, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The first period of research on resilience in Indonesia found that Nurussakinah Daulay [3] studied the resilience of mothers with autistic children, Yudi Kurniawan and N. Noviza [4] studied the resilience of survivors of violence, Sari, Sari & Hernawaty [5] studied the resilience of stunting youth, Soerjoatmodjo & Moningka [6] studied mental interventions to increase the resilience of badminton athletes, Mujahidah & Listiyandini [7] studied the effect of resilience and empathy on depressive symptoms in adolescents, Izzaturrohmah and Nuristighfari Masri Khaerani [8] studied the resilience of women victims of violence, Maesaroh, Sunarti, and Muflikhat [9] studied the resilience of adolescents, Intan Mutiara Mir'atannisa, Nandang Rusmana and Nandang Budiman [10] studied positive adaptability through resilience, attachment to significant figures, resilience, and delinquency among adolescents, Hidayat & Nurhayati [11] studied the effect of social support and hope on resilience in adolescents, Puspitasari, Maslihah & Wulandari [12] studied the effect of attachment on psychological well-being mediated by resilience. The second period, can be traced to Akbar & Mauna [13] which studied the protective factors of the resilience of Special School teachers, Yuliastutik & Fitrianur [14] studied the relationship of self-efficacy to adolescent resilience during a pandemic, Rahmawati, Suhari, Astuti & Musviro [15] studied adolescent resilience after a disaster, Batubara, Daulima, Wardani, Kusumawati, Setiyawan, Oktariani & Rumiyati [16] examined the resilience of young survivors of domestic violence, Rahayu & Ediati [17] examined self-love and resilience of students and Dwiputri & Harsono [18] regarding the relationship between social support and resilience of Qur'an memorizing students, Hermahayu [19] studied the resilience of athletes, Dyah Triarini Indirasari, Debora Eflina Purba, Rizka Anindita [20] studied the mediation role of resilience, Ahrul Azumar, Sokhivah, and Ati Kusmawati [21] studied the resilience of athletes with severe injuries, Edwin Adrianta Surijah, Gaura Hari Prasad, and ~ 114 ~ Made Rinda Ayu Saraswati [22] studied marital resilience and satisfaction, Dewi Khurun Aini, Marcus Stück, Lucky Ade Sessiani, Darmuin [23] studied the resilience of adolescents during a pandemic, Nadya Ariyani Hasanah Nuriyyatiningrum, Ahmad Gimmy Prathama Siswadi, Achmad Djunaidi, Quadri Mojeed Akorede [24] studied the resilience o...…”
Section: Introductionmentioning
confidence: 99%